Understanding the Progression of Function and Psychological Readiness of Pre-Adolescent Athletes Following Anterior Cruciate Ligament Reconstruction. Issue 5 (31st May 2022) - Greenberg, Elliot M.; Dyke, Julie; Link, Meredith; Todd Lawrence, J.; Ganley, Theodore
Background: Patient reported outcome measures (PROM) allow for a comprehensive assessment of physical and emotional factors not accounted for by functional performance testing after anterior cruciate ligament reconstruction (ACLR). The ACL-RSI gauges an athlete's psychological readiness to return to sport and recent evidence suggest this measure may help identify individuals at risk of secondary injury. Our current knowledge of how physical function and psychological preparedness change during recovery after ACLR in youth athletes it limited. Understanding the change and interplay between these factors will help optimize rehabilitation and improve patient care. Purpose: The purpose of this study was to evaluate changes in psychological readiness (ACL-RSI), knee related function (Pedi-IKDC) and generalized activity (Pedi-FABS) throughout the course of rehabilitation in a group of pre-adolescents after ACLR. Methods: A prospective observational cohort study of pre-adolescent athletes who underwent ACLR within a single institution. All subjects had surgery between 12/2017-12/2020 and followed institutional specific protocol emphasizing clinical rehabilitation for a duration of 7-9 months. Subjects completed a series of PROM (ACL-RSI, Pedi-IKDC and Pedi-FABS) quarterly for the initial 12 months following ACLR. Friedman's test for repeated measures and Wilcoxon Matched Pairs Signed Ranks Test with a Bonferonni correction (p <= 0.017) was used to determine if differences existed amongst each measure over time. Results: A total of 28 subjects were included in this analysis (21 male; mean age 12.43 ± 1.40 yrs). Pedi-FABS and Pedi-IKDC both demonstrated significant changes from 3 months (Pedi-FABS 2.63 ± 3.95, Pedi-IKDC 70.84 ± 11.36) to 6 months (Pedi-FABS 9.9 ± 8.55, Pedi-IKDC 87.05 ± 8.03) and from 6 to 9 months (Pedi-FABS 16.57 ± 6.88, Pedi-IKDC 94.40 ± 5.24) (p <= 0.017)(Figure 1 & 2). ACL-RSI approached significance for 3 months (57.81 ± 24.73) to 6 months (70.36 ± 19.77) (p = 0.019) and was definitively significant for changes between 6 to 9 months (85.83 ± 11.02) (p = 0.003) (Figure 3). No significant change was observed between 9-12 months post-operatively for any of these measures. Conclusion: In preadolescent athletes, steady improvements in generalized activity and knee function occur during the first 9 months following ACLR. Psychological readiness to return to sport trended upwards, but didn't reach statistical significance until later in recovery. Beyond 9 months, physical function and psychological preparedness remain largely unchanged. These data support a prolonged recovery period is required to maximize self-reported function and psychological readiness after ACLR in preadolescent athletes. Figure 1. Median and Percentile distribution of Pedi-FABS scores over the initial 12 months following ACLR. Significant change in score was found to be from both 3 to 6 months and 6 to 9 months (p = 0.007 and 0.004, respectively) Figure 2. Median and Percentile distribution of Pedi-IKDC scores over the initial 12 months following ACLR. Significant change in score was found to be from both 3 to 6 months and 6 to 9 months (p = 0.000 and 0.001, respectively) Figure 3. Median and Percentile distribution of ACL-RSI scores over the initial 12 months following ACLR. Nearly significant change in score was noted from 3 to 6 months (p = 0.019). Significant change in score was found to be from 6 to 9 months (p = 0.003)